The Influence of Telemedicine Care on the Management of Behavioral and Psychological Symptoms in Dementia (BPSD) Risk Factors Induced or Exacerbated During the COVID-19 Pandemic - Soares, Walter Barbalho; Silvestre, Ingrid Tinôco; Lima, Amannda Melo de Oliveira; de Almondes, Katie Moraes (Frontiers in Psychiatry, 2020)
The number of people with dementia worldwide is expected to increase to approximately 1.3 billion in 2050. Almost 90% of patients diagnosed with dementia suffer from behavioral and psychological symptoms of dementia (BPSD). BPSD causes and risk factors are multiple and complex and it can be responsible for hospitalizations in long-term institutions, psychiatric hospitalizations and search for health services. Recently, the world imposition of social distance and self-isolation as the best preventive measures for COVID-19 pandemic is creating challenges in the health care and management of this population, which may trigger or aggravate BPSD; and most of the caregivers are not prepared to deal with it. In face of this actual social distancing, telemedicine comes to be a tool for improving the management of these acute symptoms and mental care. In this article, we discuss and disseminate recommendations on this important alternative of assistance, especially considering the cases of BPSD. In this context of a pandemic, even patients with BPSD and caregivers require more frequent and updated guidance, considering the difficult context to social distance. Telemedicine can reduce the risk for development of negative outcomes in mental health precipitated by reduction of social contact and less access to health services, improving dementia symptoms management, mainly BPSD